Sensor arrays based in a hydropower dam allow synoptic observations of water quality variations in a large river - Twiss, Michael R.; Skufca, Joseph D.; Ridal, Jeffrey J.; Loftus, Sarah E.; Sprague, Heather M.; Neff, Faith C.; Lumbrazo, Cassie; Russo, Anthony; Mimouni, El Amine; St-Pierre, Luc (Frontiers in Water, 2026)
Methods to observe changes in water quality in large rivers are constrained by differing water masses due to tributaries and nearshore influences as well as logistical challenges presented by seasonal constraints such as freezing in winter. A novel method was developed to monitor seasonal water quality at high temporal resolution in the Upper St. Lawrence River (annual average discharge of 7,250 m3·s−1). The method utilized hydrodynamic modeling combined with upstream surveys using vessels to characterize water masses (via transverse and longitudinal transects) influencing water quality observed by automated sensor arrays and discrete water sample collection at fixed stations located in a run-of-the-river hydropower dam. The sensor locations in the dam were based on hydrodynamic modeling used to hind-cast water sources upstream that passed through the sensors that draw water from water turbine intakes. The advantages of the fixed (Eulerian) protocol with sensors in specific locations outweigh vessel and buoy-based sensor arrays since they have lower cost to operate, secure and safe access, simpler logistics, and provide year-round observational capacity for this large river that freezes over annually. The results demonstrate that this approach of characterizing water masses using a combination of hydrodynamic modeling with high spatial resolution water quality surveys for selection of fixed sensor locations can be applied to other hydropower dams in the Great Lakes region and large rivers elsewhere.